High-conductivity reduced-graphene-oxide/copper aerogel for energy storage. (June 2019) - Zhao, Jie; Pan, Ruijun; Sun, Rui; Wen, Chenyu; Zhang, Shi-Li; Wu, Biao; Nyholm, Leif; Zhang, Zhi-Bin
Abstract: This work reports a room-temperature, solution-phase and one-pot method for macro-assembly of a three-dimensional (3D) reduced-graphene-oxide/copper hybrid hydrogel. The hydrogel is subsequently transformed into a highly conductive aerogel via freeze-drying. The aerogel, featuring reduced graphene oxide (rGO) networks decorated with Cu and Cux O nanoparticles (Cu/Cux O@rGO), exhibits a specific surface area of 48 m 2 /g and an apparent electrical conductivity of ∼33 and ∼430 S/m prior to and after mechanical compression, respectively. The compressed Cu/Cux O@rGO aerogel delivers a specific capacity of ∼453 mAh g −1  at a current density of 1 A/g and ∼184 mAh g −1  at 50 A/g in a 3 M KOH aqueous electrolyte evidenced by electrochemical measurements. Galvanostatic cycling tests at 5 A/g demonstrates that the Cu/Cux O@rGO aerogel retains 38% (∼129 mAh g −1 ) of the initial capacity (∼339 mAh g −1 ) after 500 cycles. The straightforward manufacturing process and the promising electrochemical performances make the Cu/Cux O@rGO aerogel an attractive electrode candidate in energy storage applications. Graphical abstract: Image 1 Highlights: A straightforward and simple method for producing Cu/Cux O@rGO aerogel had been developed. The Cu/Cux O@rGO aerogel exhibits rather high apparent electrical conductivity. The compressed Cu/Cux O@rGO aerogel delivers a specific capacity of ∼453 mAh g −1  at a current density of 1 A/g. The Cu/Cux O@rGO aerogel retains 38% of the initial capacity (∼339 mAh g −1 ) after 500 cycles at current density of 5A/g.